Genetic loci for Epstein-Barr virus nuclear antigen-1 are associated with risk of multiple sclerosis. (November 2016) - Zhou, Yuan; Zhu, Gu; Charlesworth, Jac C; Simpson, Steve; Rubicz, Rohina; Göring, Harald HH; Patsopoulos, Nikolaos A; Laverty, Caroline; Wu, Feitong; Henders, Anjali; Ellis, Jonathan J; van der Mei, Ingrid; et al.
Background: Infection with the Epstein-Barr virus (EBV) is associated with an increased risk of multiple sclerosis (MS). Objective: We sought genetic loci influencing EBV nuclear antigen-1 (EBNA-1) IgG titers and hypothesized that they may play a role in MS risk. Methods: We performed a genome-wide association study (GWAS) of anti-EBNA-1 IgG titers in 3599 individuals from an unselected twin family cohort, followed by a meta-analysis with data from an independent EBNA-1 GWAS. We then examined the shared polygenic risk between the EBNA-1 GWAS (effective sample size ( N eff ) = 5555) and a large MS GWAS ( N eff = 15, 231). Results: We identified one locus of strong association within the human leukocyte antigen (HLA) region, of which the most significantly associated genotyped single nucleotide polymorphism (SNP) was rs2516049 ( p = 4.11 × 10 −9 ). A meta-analysis including data from another EBNA-1 GWAS in a cohort of Mexican-American families confirmed that rs2516049 remained the most significantly associated SNP ( p = 3.32 × 10 −20 ). By examining the shared polygenic risk, we show that the genetic risk for elevated anti-EBNA-1 titers is positively correlated with the development of MS, and that elevated EBNA-1 titers are not an epiphenomena secondary to MS. In the joint meta-analysis of EBNA-1 titers and MS, loci at 1p22.1, 3p24.1, 3q13.33, and 10p15.1 reached genome-wide significance ( p < 5 × 10 −8 ). Conclusions: Our results suggest that apart from the confirmed HLA region, the association of anti-EBNA-1 IgG titer with MS risk is also mediated through non-HLA genes, and that studies aimed at identifying genetic loci influencing EBNA immune response provides a novel opportunity to identify new and characterize existing genetic risk factors for MS.